2013
DOI: 10.1371/journal.pone.0073213
|View full text |Cite
|
Sign up to set email alerts
|

COX-2-765G>C Polymorphism Increases the Risk of Cancer: A Meta-Analysis

Abstract: BackgroundChronic inflammation has been regarded as an important mechanism in carcinogenesis. Inflammation-associated genetic variants have been highly associated with cancer risk. Polymorphisms in the gene cyclooxygenase-2 (COX-2), a pro-inflammation factor, have been suggested to alter the risk of multiple tumors, but the findings of various studies are not consistent.MethodsA literature search through February 2013 was performed using PubMed, EMBASE, and CNKI databases. We used odds ratios (ORs) with confid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 90 publications
(68 reference statements)
3
10
0
Order By: Relevance
“…These results indicated that this polymorphism may contribute to cancer risks. Consistent with the previous meta-analysis (Cao et al, 2010;Liang et al, 2011;Wang et al, 2013), we found significant increased risk -765G>C polymorphism with digestive system cancer, strongly suggesting that this polymorphism may contribute to digestive system cancer pathogenesis and help to explain individual differences of host susceptibility.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results indicated that this polymorphism may contribute to cancer risks. Consistent with the previous meta-analysis (Cao et al, 2010;Liang et al, 2011;Wang et al, 2013), we found significant increased risk -765G>C polymorphism with digestive system cancer, strongly suggesting that this polymorphism may contribute to digestive system cancer pathogenesis and help to explain individual differences of host susceptibility.…”
Section: Discussionsupporting
confidence: 91%
“…Among all of these polymorphisms, the -765G>C polymorphisms in COX-2 gene were the most widely studied for their implication in cancer risk. Several meta-analyses investigating this -765G>C polymorphism of COX-2 gene with digestive system cancer risks were performed; however, the results were inconsistent for different ethnicity and cancer types (Dong et al, 2010;Liu et al, 2010;Wang et al, 2013;Yan et al, 2013). Therefore, we conducted this meta-analysis on all eligible case-control studies to estimate the overall digestive system cancer risk associated with this polymorphism.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the previous meta-analysis (Jiang et al, 2007;Liu et al, 2010;Wen et al, 2013;Wang et al, 2013), we found significant increased risk -765G>C polymorphism with GC, strongly suggesting that this polymorphism may contribute to GC pathogenesis and help to explain individual differences of host susceptibility. After subgroup analyses according to ethnicity, we found that the variant C allele carriers (CC+GC) had a 79% increased risk of GC in Asians, but not in Caucasians.…”
Section: Discussionsupporting
confidence: 92%
“…Since we calculated sample power using the following setting, α = 0.05, β = 0.80, effect size = 0.529, σ = 0.349 (SD value of intestinal metaplasia based on the Kyoto classification in COX-2 1195 AA genotype) and δ = 0.10 (the difference between the mean value of intestinal metaplasia based on Kyoto classification in COX-2 1195 AA genotype and that in COX-2 1195 G-carrier genotype), 98 COX-2 1195 AA genotype and 98 COX-2 1195 G-carrier genotype were sufficient to identify clinically relevant differences in H. pylori -infected gastritis patients based on sample size calculation. Although previous studies have used larger numbers of samples to assess COX-2 genotypes in gastric cancer [24,25,26], we determined that 100 COX-2 1195 AA genotypes and 171 COX-2 1195 G-carriers genotype were sufficient to identify relevant in H. pylori -infected gastritis patients in this study.…”
Section: Methodsmentioning
confidence: 94%